Student and Teacher Collaboration in Developing STEM-Based Learning Modules and Pancasila Student Profiles - Fajrin, Cici Eka; Ningsih, Siti Widia Wati; Kartini; Saputra, Ady; Khoiriyah, Umi; Duma, Mariance (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2023)
Implementing an independent curriculum in Indonesia urges teachers to develop learning modules. However, conditions in elementary schools indicate that teachers still need to receive training related to teaching modules following the independent curriculum. Therefore, this study aims to develop a product in the form of a valid and effective STEM-based learning module and Pancasila Student Profile. The type of research is Research & Development (R&D) regarding the Analysis, Design, Development, Implementation, and Evaluation (ADDIE) development model. The developed product was tested on fourth-grade students at one of the elementary school levels. The results of product quality materials are assessed from expert judgment, language, media, and practitioners. The learning module developed obtained an average score of 94.5%, categorized as very feasible. The results of student responsiveness to the learning module obtained an average of 85.5% with an exciting category. The learning module has succeeded in streamlining learning outcomes and student character formation. The implementation of the learning module successfully reflects the character formation of the Pancasila Student Profile in critical reasoning, independence, and cooperation. Thus, in elementary schools, learning is needed that is oriented to the STEM model and efforts in forming the character of the Pancasila Student Profile so that the compiled modules are considered to be used in the learning of fourth-grade elementary school students.